Application of essential oils as natural biopesticides; recent advances - Assadpour, Elham; Can Karaça, Aslı; Fasamanesh, Mahdis; Mahdavi, Sahar Akhavan; Shariat-Alavi, Mahya; Feng, Jianguo; Kharazmi, Mohammad Saeed; Rehman, Abdur; Jafari, Seid Mahdi (Informa UK Limited, 2023)
There is an urgent need for the development of sustainable and eco-friendly pesticide formulations since common synthetic pesticides result in many adverse effects on human health and the environment. Essential oils (EOs) are a mixture of volatile oils produced as a secondary metabolite in medicinal plants, and show activities against pests, insects, and pathogenic fungi. Their chemical composition is affected by several factors such as plant species or cultivar, geographical origin, environmental conditions, agricultural practices, and extraction method. The growing number of studies related to the herbicidal, insecticidal, acaricidal, nematicidal, and antimicrobial effects of EOs demonstrate their effectiveness and suitability as sustainable and environment-friendly biopesticides. EOs can biodegrade into nontoxic compounds; at the same time, their harmful and detrimental effects on non-target organisms are low. However, few biopesticide formulations based on EOs have been turned into commercial practice upto day. Several challenges including the reduced stability and efficiency of EOs under environmental conditions need to be addressed before EOs are widely applied as commercial biopesticides. This work is an overview of the current research on the application of EOs as biopesticides. Findings of recent studies focusing on the challenges related to the use of EOs as biopesticides are also discussed.
Keywords: Insecticides; Herbicides; Biological Control Agents; Oils, Volatile; Animals; Humans; Pesticides; Pest Control, Biological; Acaricides